2014
DOI: 10.1002/jsfa.6730
|View full text |Cite
|
Sign up to set email alerts
|

Rice fortification with zinc during parboiling may improve the adequacy of zinc intakes in Bangladesh

Abstract: Addition of zinc sulfate to soaking water during parboiling increases the zinc content of rice and, if found to be bioavailable, could substantially reduce the prevalence of inadequate zinc intake by children and women in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Around the world, rice fortification has proved to be an effective strategy for improving vitamin and mineral intakes and status [ 19 , 20 ], thereby reducing micronutrient deficiencies [ 17 , 21 ] and anemia [ 20 , 22 ]. In recent years, many of the technical challenges of implementing rice-fortification programs have been overcome, and large-scale rice-fortification projects have been implemented in Brazil, Indonesia [ 23 ], Costa Rica, and the Philippines [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, rice fortification has proved to be an effective strategy for improving vitamin and mineral intakes and status [ 19 , 20 ], thereby reducing micronutrient deficiencies [ 17 , 21 ] and anemia [ 20 , 22 ]. In recent years, many of the technical challenges of implementing rice-fortification programs have been overcome, and large-scale rice-fortification projects have been implemented in Brazil, Indonesia [ 23 ], Costa Rica, and the Philippines [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…No other studies have reported zinc retention after refrying beans. The higher affinity of zinc to phytic acid [57], the relatively high zinc amount trapped in the pericarp rich in phytic acid after soaking and steaming rice [58], and lower zinc retention in lpa beans during boiling soaked beans suggest that during soaking and cooking, zinc from the cotyledon in non-lpa beans possibly interacted with the phytic acid, preventing excessive zinc losses in the soaking and cooking water. However, phytic acid in lpa beans was found in relatively low quantities, and the zinc from these beans may not have interacted much with the limited amounts of phytic acid remaining, causing larger zinc losses in the soaking and cooking water.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in zinc TR when rice was soaked in water with high zinc concentration (50-400 mg L −1 ) for fortification purposes was observed in previous studies. 20,21 However, zinc concentration when using HARD was lower than that used in fortification studies and was not able to increase zinc TR of parboiled samples. Water with hardness up to 133 mg L −1 CaCO 3 equivalents did not affect the TR, suggesting that other minerals present in soft to moderately hard water do not affect zinc and iron TR in milled parboiled rice.…”
Section: Resultsmentioning
confidence: 95%